Alumina Surface Treated Pigmentary Titanium Dioxide with Suppressed Photoactivity - Veronovski, N.; Lesnik, M.; Verhovsek, D. (Journal of Coating Science and Technology, 2014)
The aim of the optimization of the technological process was to coat the surface of the pigment in a controlled manner and to supress photoactivity in the titanium dioxide (TiO2) pigment. As part of this research, a systematic approach to TiO2 pigment surface treatment with alumina was conducted. Surface treatment with alumina plays a significant role in the improvement of TiO2 properties (e.g. weather resistance and photostability). This research encompasses a raw material analysis and process conditions study. Sodium aluminate and aluminium sulphate were used as a source of alumina hydroxide. The effectiveness of surface treatment was determined using scanning-transmission (STEM) and transmission (TEM) electron microscopy. The photoactivity of pigmentary TiO2 was determined before and after surface treatment. A controlled surface treatment process resulted in pigmentary TiO2 particles with uniform amorphous layers, which supressed the photoactivity of the pigment.